PENGARUH PROMOSI TERHADAP LOYALITAS NASABAH DI PT. BANK MANDIRI KANTOR CABANG DOTULOLONG LASUT MANADO. - MELKA DODAI KOYONG; SONTJE SUMAYKU; JHONY KALANGI (Universitas Sam Ratulangi, 2016)
Abstract PT. Bank Mandiri Branch Office Dotulolong lasut Manado realized that to stimulate customer loyalty, then the sale becomes important in influencing the loyalty of its customers. The purpose of this study was to determine whether there is a relationship between customer loyalty promotion with the PT. Bank Mandiri Branch Office Dotulolong Lasut Manado. The method used in this research is quantitative method associative approach and datasource are customers of PT. Bank Mandiri Branch Office Dotulolong Lasut Manado. The result showed that, there is a significant relationship between promotion with customer loyalty in the PT. Bank Mandiri Branch Office Dotulolong Lasut Manado, where the relationship is detected at r = 0.73 .Perhitungan KP detected that the factors determining the sale of 52.8% Changes in customer loyalty factor while 42.8% Changes in customer loyalty determined other factors. It is recommended that PT Bank Mandiri Branch Office Manado keep doing promotion to continue to stimulate the customer so that it can improve their Clients Loyalty. This also will affect postitif not only short term but also for the long term. Keywords: Promotion, Customer Loyalty.